Cover Image. Issue 11 (2nd November 2022) - Shkil, Fedor; Kapitanova, Daria; Borisov, Vasily; Veretennikov, Nikolay; Roux, Natacha; Laudet, Vincent
Abstract : The developing pectoral fin of Clarias gariepinus, which displays an alternative fin pattern characterized by a lack of the larval stage typical of other teleosts (11 dpf, SL = 8.5 ± 0.5 mm). A confocal image (phalloidin and DAPI staining) of the ventral side of the catfish larvae; From: Direct development of the catfish pectoral fin: An alternative pectoral fin pattern of teleosts ; Shkil F, Kapitanova D, Borisov V, Veretennikov N, Roux N, Laudet V; https://doi.org/10.1002/dvdy.509